Effect Of Shredded Recycled Powder Free Latex Gloves On The Properties Of Hollow Concrete Block - Aznan, Noor Nabila (Universiti Sains Malaysia, 2019)
Malaysia is one of the biggest producer and exporter of examination and surgical glove in the world and glove industry dominates approximately 70% of all rubber products exports in the country, supplying close to 60% of the world consumption. However, latex products manufacturing industry is still faced with mitigating with rejected glove such as glove does not meet specifications required. In order to save latex glove from landfills sustainable methods of waste disposal such as recycling, composting and upcycling are being evaluated. For these reasons, study on the effects of using latex glove is needed to observe the potential to replacing latex glove as a fine aggregate in concrete. Concrete blocks were prepared at 5% of shredded powder free latex gloves (PFLG) replacements levels using water to cement ratio of 0.5. The mix used in this research is dry mix. Several tests were conducted to concrete block namely, compressive strength, water absorption, initial rate of suction, density test and dimensions and tolerances. As a result, the replacement of 5% shredded PFLG, reduce the strength of the concrete block. It was found that the PL concrete block absorb more water compared than the control concrete block. The density of PL concrete block lighter than control concrete block due to the replacement of shredded PFLG in the concrete block. The replacement of shredded PFLG in concrete block decreases the initial suction rates because PFLG do not absorb water.